Power of Tax Authorities, Tax Morale , and Tax Compliance:A Mediation Analysis in East Malaysia - Mohd Allif Anwar Abu Bakar; Mohd Rizal Palil; Ruhanita Maelah; Mohd Helmi Ali (Universiti malaya, 2022)
Manuscript type: Research paperResearch aims: This paper aims to scrutinise the association between the power-based model (power of tax authorities) and sociopsychological factors (tax morale) in the theoretical framework of the tax compliance modelDesign/Methodology/Approach: A survey was completed by 116 self-employed and salaried individuals in East Malaysia. Partial Least Squares-SEM (PLS-SEM) was employed to analyse the data.Research findings: The results show no impact of the power of tax authorities (coercive and legitimate power) on tax compliance. Only the coercive power of tax authorities has a significantly positive effect on tax morale. However, a significant negative relationship was found between tax morale and tax compliance. Finally, tax morale is proven to mediate coercive power and tax compliance.Theoretical contribution/originality: The study adds to the body of knowledge by including the power of tax authority and tax morale in a tax compliance model. Theoretically, this study contributes to the literature that moral consideration should not be overlooked in its mediating value between the power of tax authorities and tax compliance. Practitioner/policy implications: The present study provides novel insight into how tax administrators, especially the Inland Revenue Board of Malaysia (LHDN), utilise their power to influence tax morale and tax compliance.